The cauldron of story : a theory of narrative - Pavlik, Anthony John. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
Stories are as old as the ability of human beings to communicate, and every culture both historically and geographically, appears to have its own body of narratives. Since the early Greeks, different theories of the nature of narrative have been advanced, but the general tenor of the arguments presented has usually been to view narrative as an inferior form of knowledge. This thesis aims to examine one theory of narrative that sets itself at odds with this position: Walter Fisher's "narrative paradigm". This theory seeks to re-unite mythos and logos through its notions of coherence and fidelity and the logic of good reasons, and, following an explication of the theory, it will be assessed through its application to a genre of literature, children's literature, in the form of J.K. Rowling's Harry Potter novels.
Keywords: Narration (Rhetoric); Potter, Harry (Fictitious character); Children's stories, English -- History and criticism.